PENGARUH JARAK PELAPISAN PADA PROSES THERMAL SPRAY ALUMINIUN (TSA) TERHADAP KEKUATAN IKATAN COATING DAN KETEBALAN LAPISAN PADA BAJA AISI 1020 - Ismail, Pitrah Rapi; Sri Hastuti; Catur Pramono; Nurhadi Nurhadi; Wibowo, Rheza Ari; Akhmad Nurdin; Hassany, Ibnu Rosyid Al; Bramono Pandu (ELEMEN : JURNAL TEKNIK MESIN, 2024)
Thermal spray arc is a familiar coating method used around 100 years ago. This coating technique was chosen to reduce damage and improve the surface quality of materials with coating bonds that are in direct contact with extreme marine environments. The minimum thickness of the TSA coating is around 100 – 500 µm. According to NACE/AWS/SSPC, a coating layer submerged in seawater will lose 20 µm every year, for a minimum bond strength of 6.89 Mpa. The research aims to analyze the effect of coating distance on AISI 1020 steel. The tests carried out are dry film thickness, pull of adhesive, and bending tests. This research uses distance variations of 150 mm, 250 mm, 350 mm. The research results show that the use of distance has an effect on the bond strength of the layer and the substrate. The best bond strength and bending ability values ​​were found at a distance of 350 mm, with a coating strength of 10.81 Mpa and no bending cracks. Increasing distance variations in the thermal spray process increases bond strength and bending ability.